Evaluation of Cathodic Protection Criteria for Embedded Steel Reinforcement in concrete structures - Dolli, Hirudayasamy; Kavitha, Andiappan; ., Jeevarose (International Journal of Engineering and Technology, 2018)
This paper presents the results of performance of sacrificial protection in preventing the rebar corrosion in chloride contaminated and chloride free concrete. In this present study, the effectiveness of sacrificial protection of embedded steel rebars has been evaluated on chloride contaminated and chloride free concrete slabs using ribbon type Zinc anodes with ion conductive polymer backfill over a period of 250 days of exposure. The results showed that the ribbon type zinc sacrificial anodes with the navel electrochemical interface (Ion conductive polymer backfill) can confer effective corrosion protection of embedded steel in concrete on preventing corrosion initiation in chloride contaminated as well as chloride free concretes slabs. The cathodic protection criteria evaluated on concrete unit slab showed that 100-150mV is necessary in the atmospheric exposure and 160-200mV under alternate wetting & drying conditions.Â